An analysis of whole-body kinematics, muscle strength and activity during cross-step topspin among table tennis players - Chen, M.-Z.; Wang, X.; Chen, Q.; Ma, Y.; Lanzoni, I. M.; Lam, W.-K. (International Journal of Performance Analysis in Sport, 2022)
This study examined the differences of muscle strength, electromyography (EMG) and whole-body kinematics during maximum cross-step table tennis topspin between advanced and intermediate players. Ten advanced and ten intermediate players performed both voluntary isokinetic contraction test and forehand topspin strokes with maximum-effort towards cross-court target zone. The results indicated that advanced players generated significantly greater maximum racket speeds during forward swing phase (P < 0.05). At the instant of the topspin stroke, significantly smaller shoulder horizontal flexion and elbow flexion angles, but larger joint angular velocities in advanced players (P < 0.05). Moreover, advanced players exhibited longer muscle firing duration of anterior deltoid and biceps brachii as well as higher root mean squares and EMG integrals of the abdominal external oblique, anterior deltoid and biceps brachii muscles than the intermediate players (P < 0.05). Furthermore, the isokinetic results showed higher shoulder abduction/adduction, hip flexion/extension and knee flexion torques at fast speed (240°/s) and higher elbow flexion torque at medium speed (120°/s) in advanced players (P < 0.05). The findings suggest that higher activation of the deltoid, biceps and abdominal external oblique muscles as well as larger muscle strength under higher speed conditions would be the plausible key factors to maximise racket and joint angular velocities in forehand topspin.